2019
DOI: 10.1101/662510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Parvalbumin-positive Interneurons in Auditory Steady-State Response Deficits in Schizophrenia

Abstract: Despite an increasing body of evidence demonstrating subcellular alterations in parvalbumin-positive (PV + ) interneurons in schizophrenia, their functional consequences remain elusive. Since PV + interneurons are involved in the generation of fast cortical rhythms, these changes have been hypothesized to contribute to well-established alterations of beta and gamma range oscillations in patients suffering from schizophrenia. However, the precise role of these alterations and the role of different subtypes of P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The Ex-SZTR cell state is predominantly associated with superficial-layer excitatory neurons (layers II/III), whereas cortico-cortical excitatory neurons are enriched for layer V. The observed layer-specificity of perturbations is consistent with the enrichment of schizophrenia genetic variants proximal to genes preferentially expressed in layer II and layer V 59 . Among inhibitory neurons, we detected the strongest association between schizophrenia DEGs and genomic variants in In-PV-Basket cells, consistent with the known dysregulation of PV-expressing GABAergic neurons in schizophrenia hypothesized to contribute to the disruption of synchronous neural activity in schizophrenia 60,61 . Unlike neuronal populations, we did not observe any significant association between patterns of differential expression and genetic association in either glial or endothelial cells, suggesting non-neuronal cell types do not play a primary role in schizophrenia pathologies mediated by transcriptional dysregulation.…”
Section: Introductionsupporting
confidence: 82%
“…The Ex-SZTR cell state is predominantly associated with superficial-layer excitatory neurons (layers II/III), whereas cortico-cortical excitatory neurons are enriched for layer V. The observed layer-specificity of perturbations is consistent with the enrichment of schizophrenia genetic variants proximal to genes preferentially expressed in layer II and layer V 59 . Among inhibitory neurons, we detected the strongest association between schizophrenia DEGs and genomic variants in In-PV-Basket cells, consistent with the known dysregulation of PV-expressing GABAergic neurons in schizophrenia hypothesized to contribute to the disruption of synchronous neural activity in schizophrenia 60,61 . Unlike neuronal populations, we did not observe any significant association between patterns of differential expression and genetic association in either glial or endothelial cells, suggesting non-neuronal cell types do not play a primary role in schizophrenia pathologies mediated by transcriptional dysregulation.…”
Section: Introductionsupporting
confidence: 82%
“…Biophysical modeling could further allow us to develop a revised taxonomy of the different oscillations, by predicting which circuit components each oscillation arises from [48,[59][60][61]. This type of modeling can be taken a step further by delineating how circuit features contribute to oscillation event dynamics that support particular aspects of auditory processing, such as speech tracking [62][63][64] or auditory steady-state responses [65][66][67]. A clearer understanding of the mechanisms creating oscillations will also pave the way to improving neuropathologies associated with disrupted brain rhythms, via pharmacology or targeted neuromodulation that normalizes rhythmic activity in a principled manner [68].…”
Section: Mechanisms Of Oscillation Generationmentioning
confidence: 99%
“…We used a simple computational model consisting of an excitatory population, representing pyramidal cells, and an inhibitory population, representing PV + inhibitory interneurons. While most of the experimental evidence for a reduction in GAT1, which in turn would lead to an increase in IPSC decay times, points towards chandelier cells [25], we have previously shown that at realistically low ratios of chandelier cells to basket cells in a microcircuit, gamma and beta range ASSR changes as seen in SCZ patients, are most likely due to an increase of IPSC decay times at basket cell synapses [32]. Our simplified model does not incorporate other types of inhibitory interneurons such as somatostatin-positive (SST + ) or vasoactive intestinal peptide-positive (VIP + ), although they have been shown to play important functional roles in cortical microcircuits [5].…”
Section: Discussionmentioning
confidence: 99%
“…The model proposed here is based on a recent reimplementation [28] of the simple model presented by Vierling-Claassen et al [44], which has been used in previous studies of ASSR deficits [32], and which is integrated in the ASSRUnit model database, a framework for automated testing of ASSR models against observations from empirical studies [30].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation